Environmental Impact Analysis on Residential Building in Malaysia Using Life Cycle Assessment - Abd Rashid, A.F.; Idris, J.; Yusoff, S. (MDPI, 2017)
The building industry has a significant impact on the environment due to massive natural resources and energy it uses throughout its life cycle. This study presents a life cycle assessment of a semi-detached residential building in Malaysia as a case study and assesses the environmental impact under cradle-to-grave which consists of pre-use, construction, use, and end-of-life phases by using Centre of Environmental Science of Leiden University (CML) 2001. Four impact categories were evaluated, namely, acidification, eutrophication, global warming potential (GWP), and ozone layer depletion (ODP). The building operation under use phase contributed the highest global warming potential and acidification with 2.41 × 103 kg CO2 eq and 1.10 × 101 kg SO2 eq, respectively. In the pre-use phase, concrete in the substructure has the most significant overall impact with cement as the primary raw material. The results showed that the residential building in Malaysia has a fairly high impact in GWP but lower in acidification and ODP compared to other studies.